Knockdown of XBP1 by RNAi in Mouse Granulosa Cells Promotes Apoptosis, Inhibits Cell Cycle, and Decreases Estradiol Synthesis - Wang, Nan (Int J Mol Sci, 2017)
Granulosa cells are crucial for follicular growth, development, and follicular atresia. X-box binding protein 1 (XBP1), a basic region-leucine zipper protein, is widely involved in cell differentiation, proliferation, apoptosis, cellular stress response, and other signaling pathways. In this study, RNA interference, flow cytometry, western blot, real-time PCR, Cell Counting Kit (CCK8), and ELISA were used to investigate the effect of XBP1 on steroidogenesis, apoptosis, cell cycle, and proliferation of mouse granulosa cells. ELISA analysis showed that XBP1 depletion significantly decreased the concentrations of estradiol (E2). Additionally, the expression of estrogen synthesis enzyme Cyp19a1 was sharply downregulated. Moreover, flow cytometry showed that knockdown of XBP1 increased the apoptosis rate and arrests the cell cycle in S-phase in granulosa cells (GCs). Further study confirmed these results. The expression of CCAAT-enhancer-binding protein homologous protein (CHOP), cysteinyl aspartate specific proteases-3 (caspase-3), cleaved caspase-3, and Cyclin E was upregulated, while that of Bcl-2, Cyclin A1, and Cyclin B1 was downregulated. Simultaneously, CCK8 analysis indicated that XBP1 disruption inhibited cell proliferation. In addition, XBP1 knockdown also alters the expression of Has2 and Ptgs2, two essential genes for folliculogenesis. Collectively, these data reveal a novel critical role of XBP1 in folliculogenesis by regulating the cell cycle, apoptosis, and steroid synthesis of mouse granulosa cells.